Juridical Analysis Of State Boundary Determination From The Perspectives Of International Law And Indonesian National Law - Kabella Azzahra; Rahmianti Ranti Pawari; Adystia Sunggara (Ipso Jure, 2026)
The determination of state boundaries is crucial for safeguarding sovereignty and ensuring legal certainty. As an archipelagic nation, Indonesia faces unique challenges in aligning national legislation with international standards. This study analyzes the legal framework and implementation of state boundary determination from the perspectives of international law and Indonesian national law. Using a normative legal research method with statutory and conceptual approaches, this study examines the synergy between UNCLOS 1982 and Indonesian laws, including Law No. 43 of 2008. The findings reveal that while the normative legal framework is adequate, significant legal gaps persist due to differing delimitation methods (equidistance vs. equitable principles) and unresolved unilateral claims in strategic areas like the North Natuna Sea. This study concludes that resolving these deadlocks requires stronger harmonization between domestic enforcement and international maritime jurisprudence, alongside enhanced inter-agency technical coordination.